Time-restricted feeding restores metabolic flexibility in adult mice with excess adiposity - Yan, Lin; Rust, Bret M.; Palmer, Daniel G. (Frontiers in Nutrition, 2024)
Obesity is prevalent with the adult population in the United States. Energy-dense diets and erratic eating behavior contribute to obesity. Time-restricted eating is a dietary strategy in humans that has been advanced to reduce the propensity for obesity. We hypothesized that time-restricted feeding (TRF) would improve metabolic flexibility and normalize metabolic function in adult mice with established excess adiposity. Male C57BL/6NHsd mice were initially fed a high-fat diet (HFD) for 12 weeks to establish excess body adiposity, while control mice were fed a normal diet. Then, the HFD-fed mice were assigned to two groups, either ad libitum HFD or TRF of the HFD in the dark phase (12 hours) for another 12 weeks. Energy intake and body fat mass were similar in TRF and HFD-fed mice. TRF restored rhythmic oscillations of respiratory exchange ratio (RER), which had been flattened by the HFD, with greater RER amplitude in the dark phase. Insulin sensitivity was improved and plasma cholesterol and hepatic triacylglycerol were decreased by TRF. When compared to HFD, TRF decreased transcription of circadian genes Per1 and Per2 and genes encoding lipid metabolism (Acaca, Fads1, Fads2, Fasn, Scd1, and Srebf1) in liver. Metabolomic analysis showed that TRF created a profile that was distinct from those of mice fed the control diet or HFD, particularly in altered amino acid profiles. These included aminoacyl-tRNA-biosynthesis, glutathione metabolism, and phenylalanine, tyrosine, and tryptophan biosynthesis pathways. In conclusion, TRF improved metabolic function in adult mice with excess adiposity. This improvement was not through a reduction in body fat mass but through the restoration of metabolic flexibility.